Rock scenes of wrestling in Serra da Capivara National Park, possible interpretations (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This work is based on field research out in the southeast of the State of Piauí and, later, in Alto Xingu (Central Brazil). Through a corpus of wrestling in rock records, possible inferences about these paintings were presented. Beyond just the look of researchers, remnants of original peoples, who engaged in ritualized wrestling, presented their own interpretations. In conclusion, if it was not possible to obtain the codes used by the ancestral groups that painted them in Serra da Capivara; to another extent, it was possible to reflect on the phenomenon that allows natives, nowadays, to interpret those records in their own way.
Keywords: Rock art; Serra da Capivara National Park; Scenes of wrestling